2017
DOI: 10.1080/21691401.2017.1337030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Notch signalling pathway on the relationship between vascular endothelial dysfunction and endothelial stromal transformation in atherosclerosis

Abstract: At present, with the improvement of living standards and population aging, the incidence of cardiovascular and cerebrovascular disease is on the rise and has been a serious threat to human health. Statistics show that the current death caused by cardiovascular and cerebrovascular disease has become the first cause of death has been increasing year by year. Therefore, studies on coronary heart disease and atherosclerosis (AS) have become a hot topic in clinical and basic research. In this study, the question of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The JAG1‐related signaling was retrieved in Kyoto Encyclopedia of Genes and Genomes, and the results showed that JAG1 was in the upstream of Notch signaling on Human papillomavirus infection (map05165), Breast cancer (map05224), and Endocrine resistance (map01522) signaling. Moreover, Notch signaling was associated with atherosclerosis 23,24 . Thus, it was speculated that abnormal expression of JAG1 affected Notch signaling in patients with ACS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The JAG1‐related signaling was retrieved in Kyoto Encyclopedia of Genes and Genomes, and the results showed that JAG1 was in the upstream of Notch signaling on Human papillomavirus infection (map05165), Breast cancer (map05224), and Endocrine resistance (map01522) signaling. Moreover, Notch signaling was associated with atherosclerosis 23,24 . Thus, it was speculated that abnormal expression of JAG1 affected Notch signaling in patients with ACS.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Notch signaling components were up‐regulated in luminal endothelial cells at atherosclerotic lesions and resulted in proinflammatory response and senescence of endothelial cells 23 . Another study also suggested that Notch signaling was activated in atherosclerotic model 24 …”
Section: Discussionmentioning
confidence: 97%
“…reported that the Notch-signaling pathway is associated with the occurrence and progression of AS. In addition, Mao and Jiang 17 demonstrated in a recent study of 2018 that the Notch-signaling pathway is activated in the vessels of AS animal models and inhibition of the Notch-signaling pathway can significantly improve AS. Moreover, Aquila et al 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of NICD acetylation mediates the activation of the Notch1 signaling pathway [ 26 , 27 , 46 ]. The Notch signaling pathway is reported to promote the progression of EndMT in human coronary endothelial cells and the development of atherosclerosis [ 47 ]. Our study revealed that DAPA inhibits EndMT through the SIRT1-regulated the Notch signaling pathway.…”
Section: Discussionmentioning
confidence: 99%